1999
DOI: 10.1161/01.hyp.34.4.897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cholecalciferol Treatment on the Relaxant Responses of Spontaneously Hypertensive Rat Arteries to Acetylcholine

Abstract: Abstract-We studied the effect of oral cholecalciferol treatment on the endothelium-dependent vascular relaxation and hyperpolarization induced by acetylcholine (ACh), which is impaired in spontaneously hypertensive rats (SHR). Adult female SHR and normotensive Wistar-Kyoto rat (WKY) controls received 125 g of cholecalciferol per kilogram body weight per day for 6 weeks. The responses to ACh of the isolated mesenteric vascular bed and mesenteric artery rings were measured, as well as the smooth muscle cell mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 34 publications
(45 reference statements)
2
60
1
2
Order By: Relevance
“…Association between low or deficient 25-hydroxyvitamin D and impaired brachial artery FMD was demonstrated in a general population of middle-aged and older adults and in ESRD patients (22,24). It was shown experimentally that exposure to cholecalciferol improved the relaxation response of spontaneously hypertensive rat arteries to acetylcholine (25) and that vitamin D 3 stimulated prostacyclin production by vascular smooth muscle cells (26). Moreover, studies on aortic rings of spontaneously hypertensive rats have shown that Vitamin D derivatives acutely reduce endothelium-dependent contraction by reducing calcium influx into endothelial cells and decreasing production of endothelium-derived contracting factors (27).…”
Section: Discussionmentioning
confidence: 99%
“…Association between low or deficient 25-hydroxyvitamin D and impaired brachial artery FMD was demonstrated in a general population of middle-aged and older adults and in ESRD patients (22,24). It was shown experimentally that exposure to cholecalciferol improved the relaxation response of spontaneously hypertensive rat arteries to acetylcholine (25) and that vitamin D 3 stimulated prostacyclin production by vascular smooth muscle cells (26). Moreover, studies on aortic rings of spontaneously hypertensive rats have shown that Vitamin D derivatives acutely reduce endothelium-dependent contraction by reducing calcium influx into endothelial cells and decreasing production of endothelium-derived contracting factors (27).…”
Section: Discussionmentioning
confidence: 99%
“…3 Studies in spontaneously hypertensive rats have shown decreased blood pressure on oral administration of supplemental vitamin D, as well as improvements in endothelial cell-dependent vasodilation. [5][6][7] Two cross-sectional studies examining vitamin D intake and blood pressure in humans reported conflicting results. Sowers et al examined 86 normotensive young women (20 to 35 years of age) and 222 normotensive older women (55 to 80 years of age).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Oral supplementation with vitamin D lowers blood pressure in hypertensive rats. [5][6][7] In humans, cross-sectional data suggest an association between low vitamin D intake (Ͻ400 IU per day) and higher blood pressure, 8 and a single interventional study in vitamin D-deficient elderly women found that a combination of calcium and vitamin D supplementation had a greater blood pressure-lowering effect than calcium supplementation alone. 9 However, there are no prospective data in the general population that higher vitamin D intake lowers the risk of hypertension.…”
mentioning
confidence: 99%
“…The rings of the mesenteric artery were initially balanced for one hour under 1.0g tension and washed every 10 min. The concentration-response curves for the noradrenaline (1nM to 1μM) were performed in the mesenteric arteries of the animals from the many experimental groups after preparations stabilization (15,16) .…”
Section: Evaluation Of the Mesenteric Artery Reactivitymentioning
confidence: 99%